A visible-light Paternò–Büchi dearomatisation process towards the construction of oxeto-indolinic polycycles. Issue 25 (29th April 2020) - Mateos, Javier; Vega-Peñaloza, Alberto; Franceschi, Pietro; Rigodanza, Francesco; Andreetta, Philip; Companyó, Xavier; Pelosi, Giorgio; Bonchio, Marcella; Dell'Amico, Luca
Abstract : A scalable visible-light [2 + 2]-heterocycloaddition process allows the dearomatisation of indoles to complex biorelevant polycycles. Abstract : A variety of highly functionalised N -containing polycycles (35 examples) are synthesised from simple indoles and aromatic ketones through a mild visible-light Paternò–Büchi process. Tetrahydrooxeto[2, 3- b ]indole scaffolds, with up to three contiguous all-substituted stereocenters, are generated in high yield (up to >98%) and excellent site- regio- and diastereocontrol (>20 : 1). The use of visible light (405 or 465 nm) ensures enhanced performances by switching off undesired photodimerisation side reactions. The reaction can be easily implemented using a microfluidic photoreactor with improved productivity (up to 0.176 mmol h −1 ) and generality. Mechanistic investigations revealed that two alternative reaction mechanisms can account for the excellent regio- and diastereocontrol observed.